Signalized roundabouts – capacity, traffic conditions and their influence on noise levels - Motylewicz, Marek (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
Signalized roundabouts are the suggested solution in road design, mainly due to the presence of large inner areas of accumulation for vehicles turning left, which, if designed correctly, result in a high capacity of the entire solution. In recent years, due to a dynamic growth in traffic and the deterioration of its conditions, many cities in Poland, including Bialystok, have begun rebuilding their existing intersections into signalized roundabouts. The proper functioning of such roundabouts depends on the parameters of the traffic lights signal plan and the capacity of the inner areas of accumulation, which should be larger than the traffic volume turning left. The article suggests methods of determining the capacity of these areas in the case of multi-phase signal plans, and the sample calculations have been supported by the results of traffic microsimulation modelling. Comparative calculations of the capacity of signalized roundabouts, roundabouts and intersections with no signalization have also been performed. The article also contains an analysis of the influence of signalized roundabouts on the noise level in their vicinity in relation to the results of the equivalent sound level measurements conducted in the vicinity of other types of intersections.